Does a Gravitational Aberration Contribute to the Accelerated Expansion of the Universe? (Communications in Computational Physics, 2009)
An arbitrarily small positive value of the gravitational aberration slightlyincreases the angular momentum of a two-body and multiple body system. This couldpotentially contribute to the accelerated expansion of the whole Universe. We presentsome geometrical, physical, geophysical, heliophysical, climatological, cosmological,and astronomical observational arguments, and also numerical tests to support thisconjecture. We found a remarkable coincidence between the Hubble constant and theincreasing distance of the Moon from the Earth, that is not only due to tidal forces.Numerical examples illustrating the expansion caused by the gravitational aberrationare given. This will be modeled by a nonautonomous system of ordinary differentialequations with delay.